Elementos psicológicos: narrativas en conductores de 26 a 30 años involucrados en accidentes de tránsito en Bogotá (2021)
Traffic accidents in the city of Bogotá have become a problem that must be dealt with by public health, due to the repercussions it has on society. With the use of narratives, it is intended to deepen on those psychological elements that have influence or could be triggers in the occurrence of the traffic accident, which is why the following question arises. What are the narratives about: search for sensations, altruism, locus of control, and aggressiveness in drivers between 26 and 30 years old involved in traffic accidents in the city of Bogotá?.